Comparison of susceptibility of the pest mite Brevipalpus phoenicis and the predator Agistemus brasiliensis to agrochemicals - Fuzita, Anderson Teidy; Sato, Mário Eidi; Silva, Marcos Zatti da; Nicastro, Roberto Lomba; Mendonça, Márcio José Cardoso de (Coffee Science - ISSN 1984-3909, 2014)
Among the pests that attack coffee plants (Coffea spp.), it stands out some species of phytophagous mites which can cause significant losses, such as, Oligonychus ilicis (McGregor, 1917) (Acari: Tetranychidae) and Brevipalpus phoenicis (Geijskes, 1939) (Acari: Tenuipalpidae), vector of the coffee ringspot virus (CoRSV). Recent studies have indicated that stigmaeid mites, mainly of the genera Agistemus and Zetzellia, are important natural enemies of pest mites such as B. phoenicis and O. ilicis. The objective of this study was to evaluate the effect of various chemical compounds (insecticides, acaricides and fungicides) used in coffee and/or citrus plantations (or under registration) in Brazil on the mite pest B. phoenicis and the predator Agistemus brasiliensis Matioli, Ueckermann & Oliveira, 2002 (Acari: Stigmaeidae). Various pesticides were tested, using the concentrations recommended for the control of pests on coffee or citrus plants. The applications were performed in a Potter spray tower. It was evaluated the toxicity of chemicals on the adults of both mite species, besides the effect of compounds on the instantaneous growth rates (ri) of the mites. Abamectin, profenophos + cypermethrin, deltamethrin + triazophos, diafenthiuron, fenpropathrin, spirodiclofen and etoxazole were harmfull to B. phoenicis and A. brasiliensis. Cyflumetofen and malathion caused population reductions in B. phoenicis, but did not affect the population growth of A. brasiliensis. Thiophanate-methyl affected the population growth of both species, but was more toxic to A. brasiliensis. Copper oxychloride reduced only the population growth of the predaceous mite.